Emotional quotient, healthy lifestyle dan integritas terhadap kualitas audit - Swarmilah Hariani; Roy Budiharjo; Donant Alananto Iskandar (LPMP Imperium, 2022)
This study aims to find out the Implications of Emotional Quotient, Healthy Lifestyle and Integrity on Audit Quality at BPK RI Jakarta. The population in this study are auditors who work at the Supreme Audit Agency of the Republic of Indonesia. The sampling technique in this research is random sampling, the sample is 78 respondents in AKN VI BPK RI. This research uses survey method. The results of this study are Emotional Quotient and Healthy Lifestyle have a significant impact on audit quality, while Integrity has no positive and significant impact on Audit Quality. Auditors apply ethical rules well or have high Emotional Quotient, and also Auditors who have complex tasks must always maintain their fitness so that it is necessary to apply a healthy lifestyle so that they are always primed in carrying out their audit assignments, the audit quality will tend to increase. Auditor integrity is an academic quality that will foster trust and will subsequently lead to compliance with the decisions made. In this study, the auditor's behavior is in favor of anyone and there is an interest or tactics in the audit procedure while in the field inspection process. The auditor is the spearhead of the implementation of the audit task that should be able to increase the knowledge already possessed so that the application of knowledge can be maximized in practice.